2017
DOI: 10.1212/wnl.0000000000004297
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phenotype and outcome of hepatitis E virus–associated neuralgic amyotrophy

Abstract: Patients with HEV-NA are usually anicteric and have a distinct clinical phenotype, with predominately bilateral asymmetrical involvement of, and more extensive damage to, the brachial plexus. Involvement outside the brachial plexus is more common in HEV-NA. The relationship between HEV and NA is likely to be causal, but is easily overlooked. Patients presenting with NA should be tested for HEV, irrespective of liver function test results. Prospective treatment/outcome studies of HEV-NA are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
2
10

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 23 publications
5
74
2
10
Order By: Relevance
“…A recent multi-center study demonstrated that HEV-associated NA patients tend to have more extensive and bilateral involvement of nerves, including nerves outside the brachial plexus. 6 The phenotype of our patients is in line with this conclusion, as all had three or more nerves affected, symptoms were bilateral for two, including involvement of the trunk and lower limb.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A recent multi-center study demonstrated that HEV-associated NA patients tend to have more extensive and bilateral involvement of nerves, including nerves outside the brachial plexus. 6 The phenotype of our patients is in line with this conclusion, as all had three or more nerves affected, symptoms were bilateral for two, including involvement of the trunk and lower limb.…”
Section: Discussionsupporting
confidence: 86%
“…In one patient, each of the three bouts was heralded by the intensification and spreading of the pain; in the other two, nerve lesions appeared in two phases following the resolution of pain. Multiphasic presentation was not described in the multi-center study on HEVassociated NA of van Eijk et al, 6 but it is unclear whether this information was collected. However, in one case report of HEV-associated NA, symptoms were progressive over 3 weeks, 5 and in another phrenic nerve palsy developed several months after onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are not aware of a report about the link between HEV seropositivity and reflexes impairment. Acute and chronic HEV infections may lead to extrahepatic manifestations and has been associated with neurological diseases [24, 25], including for instance, neuralgic amyotrophy [26], acute encephalitis Parkinsonism [25], and Guillain Barré syndrome [27].…”
Section: Discussionmentioning
confidence: 99%
“…18 In these cases, motor weakness and sensory disturbances are more often bilateral, asymmetric and are not confined to the brachial plexus compared to non HEV-infected patients. 19,20 The prevalence of HEV infection in patients with GBS is 5%. 21 The mechanisms by which HEV causes PTS or GBS are unknown, but it is probably an immune response induced by the virus.…”
Section: Neurolog I C Al Inj Urymentioning
confidence: 99%